2021
DOI: 10.1111/ina.12899
|View full text |Cite
|
Sign up to set email alerts
|

Affordable measures to monitor and alarm nosocomial SARS‐CoV‐2 infection due to poor ventilation

Abstract: Since the coronavirus disease 2019 (COVID‐19) outbreak, the nosocomial infection rate worldwide has been reported high. It is urgent to figure out an affordable way to monitor and alarm nosocomial infection. Carbon dioxide (CO2) concentration can reflect the ventilation performance and crowdedness, so CO2 sensors were placed in Beijing Tsinghua Changgung Hospital's fever clinic and emergency department where the nosocomial infection risk was high. Patients’ medical records were extracted to figure out their ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 58 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…By controlling the interpersonal distance, the theoretical upper limit of the patient waiting area can be calculated. For waiting space, N=int[A/d 2 ], where int [A/d 2 ] indicates that the calculation result is rounded down and d is the recommended interpersonal distance, which is 1.5m [12] . See Table 1 for the upper limit of capacity in each region.…”
Section: Methodsmentioning
confidence: 99%
“…By controlling the interpersonal distance, the theoretical upper limit of the patient waiting area can be calculated. For waiting space, N=int[A/d 2 ], where int [A/d 2 ] indicates that the calculation result is rounded down and d is the recommended interpersonal distance, which is 1.5m [12] . See Table 1 for the upper limit of capacity in each region.…”
Section: Methodsmentioning
confidence: 99%
“…CO 2 levels represent quality of ventilation and may therefore determine SARS-CoV-2 risk levels ( Lu et al, 2021 ; Meiss et al, 2021a ; Peng and Jimenez, 2021 ). Hence, determination of safe indoor CO 2 levels is recommended and could be maintained to less than 700 ppm or close to outdoor levels of less than 450 ppm ( Ahlawat et al, 2020 ; Di Gilio et al 2021 ; Eykelbosh, 2021 ; Lu et al, 2021 ). CO 2 monitors have been suggested to be placed near windows or 2 metres away from individuals and open flames ( Eykelbosh, 2021 ).…”
Section: Indoor Airmentioning
confidence: 99%
“…Instead, it has been shown that carbon dioxide (CO 2 ) can be a useful proxy for exhaled human breath and thus relative exposure risk in indoor environments. 23 25 There are limitations with this approach for students to consider: other sources of CO 2 exist, and masks and filters reduce exposure to aerosol 26 28 but not CO 2 .…”
Section: Introductionmentioning
confidence: 99%